ReCoN-Ipsundrum: An Inspectable Recurrent Persistence Loop Agent with Affect-Coupled Control and Mechanism-Linked Consciousness Indicator Assays - Sanyal, Aishik (Proceedings of the AAAI Symposium Series, 2026)
Indicator-based approaches to machine consciousness argue that evidence should be mechanism-linked, triangulated across tasks, and supported by architectural inspection and causal intervention. Inspired by Humphrey’s ipsundrum hypothesis for sentience, we implement ReCoN-Ipsundrum, an inspectable agent that extends a ReCoN state machine with a recurrent persistence loop over sensory salience N^s and an optional Barrett-inspired affect proxy reporting valence/arousal. Across fixed-parameter ablations (ReCoN, Ipsundrum, Ipsundrum+affect), we operationalize Humphrey’s qualiaphilia (preference for sensory experience for its own sake) as a familiarity-controlled scenic-over-dull route choice and find a novelty dissociation: non-affect variants are novelty-sensitive (Δscenic-entry=0.07) whereas affect coupling is stable (Δscenic entry=0.01) even when scenic is less novel (median Δnovelty≈ -0.43). In reward-free exploratory play, the affect variant shows structured local investigation (scan events 31.4 vs. 0.9; cycle score 7.6). In a pain-tail probe, only the affect variant sustains prolonged planned caution (tail duration 90 vs. 5). Lesioning feedback+integration selectively reduces post-stimulus persistence in ipsundrum variants (AUC drop 27.62, 27.9%) while leaving ReCoN unchanged. These dissociations link recurrence->persistence and affect-coupled control->preference stability, scanning, and lingering caution, illustrating how indicator-like signatures can be engineered and why mechanistic and causal evidence should accompany behavioral markers.